Can minimum prices assure the quality of professional services? - Georg Meran; Reimund Schwarze (University of Innsbruck, Department of Public Finance, 2007)
This papers studies the effects on service quality and consumer surplus of a minimum price which is fixed by a bureaucratic non-monopolistic professional association. It shows that the price set by a Niskanen-type professional assocation will maximize consumer surplus only if consumers demand the highest possible average quality. If consumers demand services of lesser quality, the association?s price will be too high if measured by consumer surplus. Moreover we show that a de-regulated market will always reproduce the favourable result of a uniformly high price in the case of top quality demand while delivering superior results in the case of a mixed demand for high and low quality services.
Keywords: L15; J44; K21; 330; liberal professions; price regulation; quality; professional association; self-regulation; EU competition policy; intrinsic motivation; Freie Berufe; Preiswettbewerb; Dienstleistungsqualität; Berufsverband; Konsumentenrente; Deregulierung; Theorie